Evaluation of InaCBGs Tariffs for BPJS Outpatient Patients as an Effort to Control Quality and Costs at the ENT Outpatient Clinic of Surabaya Islamic Hospital - Roesbiantoro, Andi; Setianto, Budhi; Adriansyah, Agus Aan; Afina, Rizka Dany; Kusumawati, Diah Retno; Sa'adah, Nikmatus (Jurnal Ilmiah Kesehatan, 2025)
This study aims to analyse shifts in demographic profiles and the distribution of BPJS healthcare service financing at the ENT Polyclinic of Surabaya Islamic Hospital from 2023 to 2024. Data indicate an increase in the proportion of adult and elderly patients, as well as a dominance of female patients. Additionally, there has been a change in the financing structure: the proportion of consultation costs has decreased, while expenditures on nursing, medications, and equipment rental have increased. The analysis of the difference between hospital tariffs and INA-CBGs claims indicates improved efficiency despite a decrease in the number of cases. The urgency of this study lies in the hospital's need to adapt to changes in patient characteristics, which are increasingly dominated by the elderly with chronic disease risks, potentially increasing the cost burden. This situation is relevant to national challenges in maintaining the sustainability of the JKN scheme and improving service quality based on accreditation. The results of this study are expected to serve as a basis for developing more adaptive service management strategies, emphasizing the strengthening of primary care, chronic disease control, and the implementation of an integrated health information system to ensure cost efficiency and service quality.